Pengaruh Masa Simpan terhadap Karakteristik Fisik dan Mikrobiologi Yoghurt Sinbiotik Ubi Jalar Kuning (Ipomoea batatas L) - Majdiyyah, Munifa; Farida, Eko (Indonesian Journal of Public Health and Nutrition, 2023)
Background: In research on the long-term stability and shelf life of yoghurt, it was found that sweet potatoes were the only starch that performed well at three storage times, the sensory viscosity was significantly higher than the control, and samples containing starch were more accepted. The purpose of this study was to determine the effect of shelf life on the physical and microbiological characteristics of yellow sweet potato synbiotic yogurt (Ipomoea batatas L). Methods: Quantitative experimental research with RAL research design factorial pattern 3, with a shelf life difference consisting of 3 levels, duplo repetition. The free variables are the shelf life of yellow sweet potato yoghurt for 0 days, 7 days, and 14 days, and the bound variables are physical characteristics (pH content, viscosity, TAT, TPT) and microbiology (total BAL). Results: Yellow sweet potato synbiotic yoghurt with all three shelf life meets the standards, namely in TAT, TPT and Total BAL and does not meet the standards at pH and viscosity because the pH is too low and the viscosity is too thick. Conclusion: Yoghurt with a shelf life of 14 days still meets the standards and can be consumed.